Female germ cell renewal during the annual reproductive cycle in Ostariophysians fish - Wildner, Daniel Dantas [UNESP]; Grier, Harry; Quagio-Grassiotto, Irani [UNESP] (Elsevier, 2013)
The objective was to characterize female germ cell renewal during the annual reproductive cycle in two species of ostariophysian fish with distinct reproductive strategies: a siluriform, Pimelodus maculatus, in which oocyte development is group synchronous and the annual reproductive period is short; and a characiform, Serrasalmus maculatus, with asynchronous oocyte development and a prolonged reproductive period. These reproductive strategies result in fish determinate and indeterminate fecundity, respectively. Annual reproductive phases were determined by biometric and histologic analysis of gonads and interpreted according to new proposals for phase classification and stages of oocyte development (with special attention to germinal epithelium activity). Histologically, there were two types of oogonia in the germinal epithelium: single oogonia and those in mitotic proliferation. Oogonial proliferation and their entry into meiosis resulted in formation of cell nests (clusters of cells in the ovarian lamellae). Morphometric analysis was used to estimate germ cell renewal. Based on numbers of single oogonia in the lamellar epithelium, and nests with proliferating oogonia or early prophase oocytes throughout the annual reproductive cycle, oogonial proliferation and entrance into meiosis were more intense during the regenerating phase and developing phase, but decreased sharply (P < 0.05) during the spawning-capable phase. Oogonial proliferation gradually recovered during the regressing phase. We concluded that, independent of species or features of the reproductive cycle, germ cell renewal occurred during the regenerating phase, ensuring availability of eggs for the spawning event. © 2013 Elsevier Inc.
Keywords: Cell renewal; Early prophase oocyte; Oogonia; Reproductive cycle; Reproductive phase; animal; cell proliferation; Characiformes; cytology; female; fish; growth, development and aging; meiosis; oocyte; ovary; physiology; prophase; reproduction; season; Animals; Cell Proliferation; Female; Fishes; Meiosis; Oocytes; Ovary; Prophase; Reproduction; Seasons; Pimelodus maculatus; Serrasalmus; Siluriformes